Assessment of bacterial community patterns from ecologically distinct Antarctic soil environments / Chun Wie Chong - Chong, Chun Wie (2011)
It is commonly known that bacteria are ubiquitously distributed in soil environments. They are heavily involved in the biogeochemical cycles and are vital in maintaining soil ecological functions. These functional roles of bacteria are especially important in the extreme and harsh environments of Antarctica where the terrestrial trophic interactions are generally limited to microorganisms due to restricted development of terrestrial plant and animal communities. In order to assess the spatial distribution and taxonomic composition of soil bacterial community in Antarctica, soils were collected from a range of geographically and environmentally distinct locations. These included relatively milder but variable environments on Signy Island, Ryder Bay and Reptile Ridge from maritime Antarctica, more extreme and relatively less disparate locations such as Alexander Island in the transition zone between maritime and continental Antarctica, and Windmill Island on coastal continental Antarctica. The soil bacterial communities were elucidated by using different molecular methods including DGGE, T-RFLP and cloning. Different diversity measures were utilised to address different aspects of diversity and community overlap. In addition, the relationship between the spatial distribution of Antarctic soil bacteria and soil heterogeneity (i.e. variation in pH, salinity, carbon, nitrogen, water and heavy metals content) was investigated using mantel type correlations and/or multiple linear regression method. The results showed that spatial clustering was a general feature in Antarctic soil bacterial communities as it was detected across all study sites. In addition, spatial patterning can be observed in both species-based (i.e. ANOSIM, PERMANOVA, NMDS) and divergent-based (i.e. nucleotide distance, UniFrac) diversity measures. Such spatial patterns were largely influenced by environmental variations such as the presence of vegetation and/or animals, anthropogenic impact, and distance to the sea. These factors have profound impacts on the underlying soil chemical parameters. Among the latter, soil pH was shown to contribute a high proportion of explanatory value to the soil bacterial assemblage patterns. On the other hand, between ecologically similar environments, the spatial patterns were influenced by the geographical proximity of the studied locations. The strong influence of environmental and soil chemical parameters in structuring bacterial community patterns highlighted the importance of niche conservatism and habitat filtering. It was hypothesized that species tend to retain their niches and traits whereby only species with suitable traits will be preferentially selected in stressful environments. This is especially true in Antarctica where most of the soil bacterial communities constantly experience limited water and nutrient input, low temperature and constant freezing-thawing cycle. Tropical or temperate soil systems generally encompassed high bacterial richness with relatively even species distribution (each ribotype occupied <10% proportion in the clone library). In comparison, Antarctic soil have much lower bacteria diversity which is composed of a few numerically dominant (ribotypes which made up >10% of the total retrieved clones in the clone library) and genotypically related species. Furthermore, Antarctic soil might harbour large fraction of unique and novel gene pools distinct from other soil environments. This is because the retrieved sequences generally showed low similarity (<97% similarity) to the closest representatives in tropical or temperate soil environments.